QUALITY AND ECONOMIC EFFICIENCY IN MILK PRODUCTION AT S.C.D.C.B. ARAD - ANUŢA MAGDIN; AURELIA SĂLĂJEANU; DANIELA E. ILIE; RADU NEAMŢ (Scientific Papers Animal Science and Biotechnologies, 2023)
The purpose of this work was to highlight the importance of milking system on the quality and efficiency of milk production. The works were performed on 400 Romanian Simmental - Fleckvieh type cow from Research and Development Station for Bovine Raising – Arad. Milking system used consists of a milking equipment type Bradulet 2 x 14, with which milk 28 cows simultaneously. Data obtained from this study revealed a significant influence of the milking system used on the quantity, quality and economic efficiency. As a result of applying this milking technology obtain a ”clean" milk, creating the possibility of placement in the quality standards imposed by the EU.